Nanolesions induced by heavy ions in human tissues: Experimental and theoretical studies - Bleicher, Marcus; Burigo, Lucas; Durante, Marco; Herrlitz, Maren; Krämer, Michael; Mishustin, Igor; Müller, Iris; Natale, Francesco; Pshenichnov, Igor; Schramm, Stefan; Taucher-Scholz, Gisela; Wälzlein, Cathrin (Beilstein Journal of Nanotechnology, 2012)
The biological effects of energetic heavy ions are attracting increasing interest for their applications in cancer therapy and protection against space radiation. The cascade of events leading to cell death or late effects starts from stochastic energy deposition on the nanometer scale and the corresponding lesions in biological molecules, primarily DNA. We have developed experimental techniques to visualize DNA nanolesions induced by heavy ions. Nanolesions appear in cells as “streaks” which can be visualized by using different DNA repair markers. We have studied the kinetics of repair of these “streaks” also with respect to the chromatin conformation. Initial steps in the modeling of the energy deposition patterns at the micrometer and nanometer scale were made with MCHIT and TRAX models, respectively.
Keywords: DNA repair; heavy ions; microdosimetry; Monte Carlo simulations; nanolesions; radiation-induced nanostructures

(untitled) - Durante, M.; Cucinotta, F. A. (Rev. Mod. Phys., 2011)

(untitled) - Todd, P. (Adv. Space Res., 1983)

(untitled) - Jakob, B.; Durante, M. (Radiat. Res., 2012)

(untitled) - Kim, J.-A.; Kruhlak, M.; Dotiwala, F.; Nussenzweig, A.; Haber, J. E. (J. Cell Biol., 2007)

(untitled) - Pshenichnov, I.; Botvina, A.; Mishustin, I.; Greiner, W. (Nucl. Instrum. Methods Phys. Res., Sect. B, 2010)

(untitled) - Martino, G.; Durante, M.; Schardt, D. (Phys. Med. Biol., 2010)

(untitled) - Krämer, M.; Durante, M. (Eur. Phys. J. D, 2010)

(untitled) - Jakob, B.; Splinter, J.; Conrad, S.; Voss, K.-O.; Zink, D.; Durante, M.; Löbrich, M.; Taucher-Scholz, G. (Nucleic Acids Res., 2011)

(untitled) - Chiolo, I.; Minoda, A.; Colmenares, S. U.; Polyzos, A.; Costes, S. V.; Karpen, G. H. (Cell, 2011)

(untitled) - Miller, K. M.; Tjeertes, J. V.; Coates, J.; Legube, G.; Polo, S. E.; Britton, S.; Jackson, S. P. (Nat. Struct. Mol. Biol., 2010)

(untitled) - Li, X.; Corsa, C. A. S.; Pan, P. W.; Wu, L.; Ferguson, D.; Yu, X.; Min, J.; Dou, Y. (Mol. Cell. Biol., 2010)

(untitled) - Herrlitz, M.; Müller, I.; Liefke, A. L.; Becker, G.; Durante, M.; Taucher-Scholz, G. (GSI Scientific Report, 2012)

(untitled) - Iacovoni, J. S.; Caron, P.; Lassadi, I.; Nicolas, E.; Massip, L.; Trouche, D.; Legube, G. (EMBO J., 2010)

(untitled) - Natale, F.; Rapp, A.; Durante, M.; Taucher-Scholz, G.; Cardoso, M. C. (GSI Scientific Report, 2012)

(untitled) - Berger, M. J. (Methods Comput. Phys., 1963)

(untitled) - Gottschalk, B.; Koehler, A. M.; Schneider, R. J.; Sisterson, J. M.; Wagner, M. S. (Nucl. Instrum. Methods Phys. Res., Sect. B, 1993)

(untitled) - Highland, V. L. (Nucl. Instrum. Methods, 1975)

(untitled) - Khan, R.; Herrlitz, M.; Jakob, B.; Durante, M.; Taucher-Scholz, G. (GSI Scientific Report, 2012)